Preterm delivery and neonatal meningitis due to transplacental acquisition of non-typhoidal Salmonella serovar montevideo. (29th May 2014) - Rai, Birendra; Utekar, Tushar; Ray, Raja
Abstract : A male infant was born at 34 weeks' gestation to a primigravida mother. The mother had a history of 1 day of diarrhoea and mild fever 8 days prior to delivery. Her blood culture was negative during the illness and her stool did not grow any pathological organism. The baby had poor feeding during the first day of his life followed by hypoglycaemia and episodes of seizure on day 2 and 3 of life. Blood culture of the baby and placental swab from the mother grew Salmonella serovar montevideo . Both baby and mother were treated with a course of cephalosporin for 21 and 7 days, respectively. Although non-typhoidal Salmonella often causes gastroenteritis in normal humans, it can cause invasive diseases in immunocompromised hosts and people at extremes of ages. Transplacental spread of Salmonella needs consideration in favourable epidemiological scenarios as its implications on fetal and newborn's life are serious.